2023
DOI: 10.3390/ijms24021351
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response in Human Jurkat T Lymphocytes to a near Physiological Hypergravity Environment and to One Common in Routine Cell Culture Protocols

Abstract: Cellular effects of hypergravity have been described in many studies. We investigated the transcriptional dynamics in Jurkat T cells between 20 s and 60 min of 9 g hypergravity and characterized a highly dynamic biphasic time course of gene expression response with a transition point between rapid adaptation and long-term response at approximately 7 min. Upregulated genes were shifted towards the center of the nuclei, whereby downregulated genes were shifted towards the periphery. Upregulated gene expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, H3K9me3 changes appear to be linked to distinct mechanistic processes, potentially influenced by force-induced chromatin remodeling mediated by LINC components [85,86]. The experiment revealed maximal H3K9me3 levels after 15 min hypergravity, coinciding with gene expression downregulation observed in previous transcriptomics analyses under similar conditions [24,87]. However, after 1 h of centrifugation, H3K9me3 returned to control values, suggesting a homeostatic adaptation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, H3K9me3 changes appear to be linked to distinct mechanistic processes, potentially influenced by force-induced chromatin remodeling mediated by LINC components [85,86]. The experiment revealed maximal H3K9me3 levels after 15 min hypergravity, coinciding with gene expression downregulation observed in previous transcriptomics analyses under similar conditions [24,87]. However, after 1 h of centrifugation, H3K9me3 returned to control values, suggesting a homeostatic adaptation.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, experiments have shown that transcriptome changes in Jurkat T lymphocytes exposed to hypergravity during suborbital rocket experiments can be replicated using an experimental centrifuge on the ground at 9× g [23]. Our previous research has also observed changes in histone modifications in Jurkat T lymphocytes [24] and cytoskeletal structures in human primary macrophages [25]. It is unknown by which means cells sense gravitational forces, but it is hypothesized that, as a mechanical force, gravity is transduced into the nucleus via the cytoskeleton, potentially changing nuclear structure, chromatin organization and subsequently transcription [26].…”
Section: Introductionmentioning
confidence: 83%
“…This void is particularly striking given the contemporary surge of interest in space biology and the concurrent application of organoids in space-related extreme conditions 2325 . Earlier deployments of biological experiments in parabolic flight have yielded some first insights into the immediate effects on cellular adhesion but only within a 2D cellular monolayer 2628 . The dataset used here is thus firmly situated within the methodological framework of inquiry driven by discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier deployments of biological experiments in parabolic flight have yielded some first insights into the immediate effects on cellular adhesion but only within a 2D cellular monolayer 26 - 28 . The dataset used here is thus firmly situated within the methodological framework of inquiry driven by discovery.…”
Section: / Cell-to-neighbourhood 3d Topology Descriptors To Identify ...mentioning
confidence: 99%